2020
DOI: 10.1155/2020/5193723
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 Polymorphisms in Plasmodium falciparum-Infected Malaria Patients

Abstract: Background and Objectives. Malaria infection, caused by Plasmodium falciparum, is the most lethal and frequently culminates in severe clinical complications. Interleukin-22 (IL-22) has been implicated in several diseases including malaria. The objective of this study was to investigate the role of IL-22 gene polymorphisms in P. falciparum infection. Material and Methods. Ten single-nucleotide polymorphisms (SNPs), rs976748, rs1179246, rs2046068, rs1182844, rs2227508, rs2227513, rs2227478, rs2227481, rs2227491,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These single nucleotide polymorphisms (SNPs) described rendered the patients either more resistant or more susceptible to malaria infection [49]. Similarly, other IL-22-related SNPs identified in different ethnicities have emerged over the years [50,51]. In line with the previous finding, elevated levels of IL-22 have been described in patients infected with Plasmodium species [52,53].…”
Section: Protozoan Infectionsmentioning
confidence: 72%
“…These single nucleotide polymorphisms (SNPs) described rendered the patients either more resistant or more susceptible to malaria infection [49]. Similarly, other IL-22-related SNPs identified in different ethnicities have emerged over the years [50,51]. In line with the previous finding, elevated levels of IL-22 have been described in patients infected with Plasmodium species [52,53].…”
Section: Protozoan Infectionsmentioning
confidence: 72%
“… 32 Aljarba et al found that rs2227481C>T located on IL‐22 could contribute to protection against P. falciparum malaria. 33 However, some studies have shown that rs2227485T>C in IL‐22 might be associated with an increased risk of papillary thyroid cancer and gastric mucosa‐associated lymphoid tissue lymphoma. 34 We demonstrated that rs2227485T>C in IL‐22 has a protective role in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…rs2227478T>C was shown to have protective effects on autoimmune thyroid disease 32 . Aljarba et al found that rs2227481C>T located on IL‐22 could contribute to protection against P. falciparum malaria 33 . However, some studies have shown that rs2227485T>C in IL‐22 might be associated with an increased risk of papillary thyroid cancer and gastric mucosa‐associated lymphoid tissue lymphoma 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Aljarba et al have reported that IL-22 polymorphisms in rs2227481 and rs2227483 are involved in the mounting of a protective immune response against Plasmodium falciparum infection. The authors also point out that the G allele of rs2227513 plays an important role in the increased production of IL-22 [73]. A recent study highlighted the role of IL-35 in malaria.…”
Section: Has An Anti-inflammatory Effect By Inhibiting Th1 Cell Differentiationmentioning
confidence: 94%